2000
DOI: 10.1074/jbc.m007210200
|View full text |Cite
|
Sign up to set email alerts
|

Human Apolipoprotein C-I Accounts for the Ability of Plasma High Density Lipoproteins to Inhibit the Cholesteryl Ester Transfer Protein Activity

Abstract: The aim of the present study was to identify the protein that accounts for the cholesteryl ester transfer protein (CETP)-inhibitory activity that is specifically associated with human plasma high density lipoproteins (HDL). To this end, human HDL apolipoproteins were fractionated by preparative polyacrylamide gradient gel electrophoresis, and 30 distinct protein fractions with molecular masses ranging from 80 down to 2 kDa were tested for their ability to inhibit CETP activity. One single apolipoprotein fracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
93
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(101 citation statements)
references
References 46 publications
8
93
0
Order By: Relevance
“…It is interesting that recent work by Gautier et al (16) has provided convincing evidence that apoC-I is the protein in HDL which accounts for the CETP-inhibitory activity that is specifically associated with human HDL. This suggests that apoC-I may be very important in determining plasma HDL-C levels, particularly when it is associated with HDL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting that recent work by Gautier et al (16) has provided convincing evidence that apoC-I is the protein in HDL which accounts for the CETP-inhibitory activity that is specifically associated with human HDL. This suggests that apoC-I may be very important in determining plasma HDL-C levels, particularly when it is associated with HDL.…”
Section: Discussionmentioning
confidence: 99%
“…Although the biological function of apoC-I in humans has not been completely elucidated, in vitro experiments have demonstrated that apoC-I has the capacity to: a ) activate LCAT (7)(8)(9); b ) inhibit lipoprotein lipase (10,11), hepatic lipase (12,13), and phospholipase A 2 (14); and c ) inhibit cholesterol ester transfer activity (15,16). ApoC-I has also been shown to play an important role in plasma TRL metabolism by inhibiting the binding and/or uptake of triglyceride emulsions or VLDL by the LDL receptor (17,18), the LDL receptor-related protein (LRP) (19,20), and the VLDL receptor (21).…”
mentioning
confidence: 99%
“…146) On the other hand, apoC-I is an inhibitor of CETP. 147,148) Transgenic mice overexpressing human apoC-I exhibit elevated levels of cholesterol and TG owing to the accumulation of cholesterol-enriched VLDL, VLDL remnants, and LDL. 149,150) In human apoC-I-transgenic mice, the elevated lipid levels are primarily associated with decreased uptake of apoB-containing lipoproteins by the liver rather than with disturbed lipolysis of lipoproteins.…”
Section: )mentioning
confidence: 99%
“…Physiologically, CETP may be regulated by at least two proteins. Apolipoprotein C-I, which resides primarily on HDL, has been reported to inhibit CETP in vitro, and studies with transgenic animals have demonstrated its ability to suppress CETP activity in vivo (6,7). Its mode of action is via modification of the surface charge of HDL, resulting in weakened CETP-HDL interactions and thus suppression of lipid transfer events with HDL (8).…”
mentioning
confidence: 99%